Proceedings of the 2019 International Conference on Organizational Innovation (ICOI 2019) 2019
DOI: 10.2991/icoi-19.2019.116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Good Governance, Tax Understanding, and Tax Sanctions on Taxpayers Compliance, Micro, Small and Medium Enterprises In Medan

Abstract: This study aims to determine how the effect of awareness such as good governance, tax understanding, and tax sanctions against taxpayers compliance, Micro, Small, and Medium Enterprises. Respondents of this research are 170 the individual taxpayer in Medan. Data analysis using Structural Equation Modeling (SEM). Hypothesis testing results show that good governance has a positive significant effect on individual taxpayer compliance, tax understanding has a positive significant effect on individual taxpayer comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The study indicated that trust in the government and perceptions of tax fairness will affect taxpayer compliance with tax regulations. Herman P. et al, (2019) determined how the effect of awareness such as good governance, tax understanding, and tax sanctions against taxpayers compliance, Micro, Small, and Medium Enterprises. The research adopted questionnaires to obtain responses using the convenient sampling technique.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The study indicated that trust in the government and perceptions of tax fairness will affect taxpayer compliance with tax regulations. Herman P. et al, (2019) determined how the effect of awareness such as good governance, tax understanding, and tax sanctions against taxpayers compliance, Micro, Small, and Medium Enterprises. The research adopted questionnaires to obtain responses using the convenient sampling technique.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…In carrying out its activities, Indonesia is in dire need of funds whose numbers are increasing every year. A significant income source in the nation is revenue from government taxes (Ajzen, 1991;Hosseini Kondelaji, Sameti, Amiri, & Moayedfar, 2016;Panjaitan, Tarmizi, Daulay, & Ginting, 2019;Olaoye, Ogunleye, & Solanke, 2019;Sasongko, Huruta, Wardani, 2019;Vergara, 2020).…”
Section: Introductionmentioning
confidence: 99%